Hydrodynamic Assessment of a Dual-Rotor Horizontal Axis Marine Current Turbine - Avital, EJ; Ai, K; Venkatesan, N; Samad, A; Korakianitis, T (International Journal of Engineering and Technology, 2018)
The hydrodynamic performance of a dual-rotor horizontal axis marine turbine (HAMCT) is investigated for the power gain in operating the rear rotor without blade-pitch control. This kind of turbine can be advantageous for a rectilinear tidal current of reversing directions, where each rotor blade is optimally fixed-pitched towards its upstream velocity. The blade element momentum (BEM) method is coupled with the Park wake model. A generic three-blade turbine is shown to gain up to 20% in the coefficient of power CP as relative to the front rotor CP when operating the rear rotor at the same tip speed ratio (TSR) as the front one, gaining overall CP up to 0.55. Analytic model is derived to backup the estimate of power gain. Plots for turbine performance variation with TSR and profile hydrodynamic efficiency are given, and analysed for lab and small-medium size turbines.Â Â